ROUNDTABLE ON EXAMINATIONS IN ACCOUNTING. - Heilman, E. A. (The Accounting Review, 1942)
At a Chicago, Illinois, meeting in 1926 one session was a roundtable on examinations in elementary accounting and the interest displayed in that program suggested that further discussion of the same topic would be welcomed. This session is therefore devoted to the subject of examinations but will consider examinations at the different levels, elementary accounting, advanced accounting, and the postgraduate C.P.A. examinations. At the Chicago meeting considerable interest was disclosed in the subject of objective examinations in elementary accounting, and it seemed at that time that the department at Minnesota had gone farther than most departments in the use of such examinations. President of the association has therefore asked the author to have a member of the staff present some materials, which they have developed in that form. A good many instructors still feel skeptical about the adaptability of this form to the held of accounting and it is hoped that this discussion will give some idea of the various types of questions which may be used and how the usual criticisms against this form may be eliminated. Objective questions are more difficult to prepare than problems and it takes a number of years of experimentation and improvement to obtain satisfactory questions and to remove flaws which necessarily appear in first attempts in this direction.